microLife. - Federation of European Microbiological Societies; European Academy of Microbiology (Oxford : Oxford University Press, 2020)
microLife is a gold Open Access journal associated with the European Academy of Microbiology (EAM) and supported by the Federation of European Microbiological Societies (FEMS), publishing full-length research articles, short reviews, and commentaries reporting research of the highest standard, novelty, and significance in the field of microbiology and related disciplines. microLife covers all aspects of microbiology ranging from molecular and evolutionary biology, physiology and genetics, environmental microbiology, chemical biology of microorganisms, microbiome research, infection and the host response to infection, to translational microbiology and microbial biotechnology. All microbes are covered including bacteria, archaea, fungi, viruses and single-celled protists, and parasites.
"microLife is an Open Access journal from FEMS and EAM, reporting research of the highest standard, novelty and significance in microbiology and related disciplines"--home page.
Description based on online resource; title from home page (viewed on April 2, 2020).
Keywords: Microbiology -- Periodicals